Theory and Practice of Model Transformations Third International Conference, ICMT 2010, Malaga, Spain, June 28-July 2, 2010. Proceedings - Tratt, Laurence; Gogolla, Martin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the Third International Conference, ICMT 2010, held in Malaga, Spain, in June 2010. The 17 revised full papers were carefully revised and selected from 58 submissions. The scope of the contributions ranges from theoretical and methological topics to implementation issues and applications. The papers include different issues related with:Search Computing, Composition of Model Deltas, Testing Model Transformation, Safe Composition of Transformations, Model-to-Model Transformations and Model Migration of Epsilon Flock.
Invited Paper -- Search Computing: A Model-Driven Perspective -- Research Papers -- Domain-Specific Composition of Model Deltas -- Temporal Model-Based Diagnostics Generation for HVAC Control Systems -- Synthesis of OCL Pre-conditions for Graph Transformation Rules -- From State- to Delta-Based Bidirectional Model Transformations -- A Constructive Approach to Testing Model Transformations -- From Sequence Diagrams to State Machines by Graph Transformation -- Safe Composition of Transformations -- Towards Incremental Execution of ATL Transformations -- Constructing and Navigating Non-invasive Model Decorations -- Model-to-Model Transformations By Demonstration -- Implementing Business Process Recovery Patterns through QVT Transformations -- Model Migration with Epsilon Flock -- Exceptional Transformations -- Improving Higher-Order Transformations Support in ATL -- Towards a Rewriting Logic Semantics for ATL -- Metamodel Matching Based on Planar Graph Edit Distance -- Surviving the Heterogeneity Jungle with Composite Mapping Operators.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Computer Communication Networks; Programming Techniques; Mathematical Logic and Formal Languages